Biobleaching of Kraft pulp using fungal xylanases produced from sugarcane straw and the subsequent decrease of chlorine consumption - Campioni, Tania Sila [UNESP] (2019)
Xylanase extract, produced by T. reesei QM9414 in a culture with sugarcane straw (SS) as substrate, was studied in the biobleaching of Kraft pulp associated with chemical bleaching. The biobleaching parameters optimization showed that 30 U/g of xylanases, at pH 5, at 50 °C, during 30 min, are the best conditions to bleach the crude Kraft pulp (3% of consistency). lA decrease of 12.5% of Kappa number, as well as the release of 1 g/lL of sugar, and the presence of chromophores compounds (237 nm) are also observed. After this xylanase biobleaching the final chlorine dioxide consumption decrease in 10%, maintaining the same brightness as in the control on the subsequent chemical process. SEM shows the effect on the pulp surface. These results clearly demonstrated that the T. reesei QM9414 xylanase is an eco-friendly and economical alternative for paper production.